2008
DOI: 10.1007/s11136-008-9405-7
|View full text |Cite
|
Sign up to set email alerts
|

Changes in health-related quality of life (HRQoL) in a population-based sample of children and adolescents after 3 years of follow-up

Abstract: In this representative, population-based sample of children and adolescents, moderate decrements in HRQoL were observed after 3 years. Changes were particularly important among girls and in relation to pubertal development. These results could provide useful reference data for other longitudinal studies in population sub-groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
51
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 34 publications
13
51
1
2
Order By: Relevance
“…These results are consistent with previous cross-sectional [1,3,16] and longitudinal studies [2,8]. According to several researchers [6,9], the causes of significantly lower scores on emotional functioning aspect of HRQoL in girls lie in extensive hormonal changes in that age, resulting in increased levels of anxiety and thereby a significant drop in psychological quality of life.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These results are consistent with previous cross-sectional [1,3,16] and longitudinal studies [2,8]. According to several researchers [6,9], the causes of significantly lower scores on emotional functioning aspect of HRQoL in girls lie in extensive hormonal changes in that age, resulting in increased levels of anxiety and thereby a significant drop in psychological quality of life.…”
Section: Discussionsupporting
confidence: 91%
“…Previous crosssectional [1,3,16] and longitudinal [2,8] studies have found similar results, i.e. the mean scores of boys tend to be considerably higher in the mentioned domains of HRQoL than those of girls.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Adolescence is a highly vulnerable stage of development; available evidence indicates a worsening of selfperceived health 20,21 and academic performance during this period. Therefore, this is a critical time that should be considered by different disciplines, including pediatrics, given that health and academic achievements in this stage have a strong effect on health and a productive life as adults.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced maturity is also linked with early substance abuse [18], alcohol abuse [19] and early sexual initiation [20]. Accordingly, a number of recent studies have documented a negative BIOLOGICAL MATURITY, AGE, QUALITY OF LIFE, KID-SCREEN 4 association between HRQoL and stage of pubertal development attained (i.e., prepubertal, pubertal, and postpubertal) [21][22], with those girls who were more advanced in their pubertal development reporting lower HRQoL scores.…”
Section: Biological Maturation As a Confounding Factor In Relations Bmentioning
confidence: 99%